GAMBARAN UMUM FEEDING PRACTICES YANG DITERAPKAN ORANGTUA PADA ANAK PICKY EATING - Santi Maria Permatasari; Farida Kurniawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTPicky eating behavior in children cause distress for parents because the impacts on children's health and family eating activities. Picky eating can be influenced by feeding practices. Feeding practices consist of restriction / control feeding, pressure to eat, and child monitoring. The purpose of this scientific literacy study is to collect a general overview on the feeding practices that applied by parents of picky eating children. The research method is a literature review using studies obtained from several databases. There are 7 quantitative studies selected with participants aged 1-12 years, and using instruments to measure picky eating and feeding practices. The result shows that parents apply pressure to eat and restriction / control feeding in feeding practices in children who exhibit picky eating behavior. This research is expected to increase parental awareness about appropriate feeding practices implemented in order to reduce the risk of children experiencing picky eating.ABSTRAKPerilaku picky eating pada anak meresahkan orangtua karena dapat berdampak pada kesehatan anak dan proses kegiatan makan keluarga. Picky eating dapat dipengaruhi dari faktor lingkungan, salah satunya feeding practices. Feeding practices terdiri atas restriction/control feeding, pressure to eat, dan monitoring child. Tujuan kajian literasi ilmiah ini adalah mengumpulkan gambaran umum studi ilmiah tentang feeding practices yang diterapkan orangtua pada anak picky eating. Metode penelitian ini adalah kajian literatur dengan menggunakan studi yang diperoleh dari beberapa database. Terdapat 7 studi kuantitatif yang terpilih dengan partisipan dalam penelitian berusia 1-12 tahun, serta menggunakan instrument untuk mengukur perilaku picky eating pada anak dan feeding practice yang diterapkan orangtua. Hasil menunjukkan orangtua menerapkan pressure to eat dan restriction/control feeding dalam feeding practices pada anak yang menunjukkan perilaku picky eating. Penelitian ini diharapkan dapat meningkatkan kesadaran orangtua mengenai feeding practice yang tepat diterapkan agar mengurangi resiko anak mengalami picky eating.